Contending visions of East Asian regional order: insights from the United States, China, Japan, and Indonesia. Issue 1 (2nd January 2019) - Singh, Bhubhindar; Teo, Sarah; Ho, Shawn; Tsjeng, Henrick
Abstract: This article challenges the simplistic view that U.S. leadership in East Asia is weakening relative to China's increasing ability to shape the regional order, which will force other states to choose between these two powers. Based on interviews with political elites, analysts, and academics in the United States, China, Japan, and Indonesia, we argue that the East Asian order transition is more complex and nuanced, especially when we examine views toward: (1) the Sino–U.S. rivalry for regional leadership; (2) whether Chinese initiatives such as the Asian Infrastructure Investment Bank and the Belt and Road Initiative disrupt the current order; and (3) the preferred vision of regional order for each of the four countries. While there is hardly a consensus view about issues of regional order, it appears that in the short to medium term, China is not expected to substantially overhaul the existing East Asian order. Nevertheless, Beijing is likely to chip away at U.S. regional leadership and, in the long term, would presumably seek to create an order that would sustain its rise and maintain its regional preponderance. The responses of other regional stakeholders toward these developments would be vital in shaping the collective impact on the East Asian order.